Changes in economic outcomes before and after rural hospital closures in the United States: A difference‐in‐differences study. (27th April 2022) - Chatterjee, Paula; Lin, Yuqing; Venkataramani, Atheendar S.
Abstract: Objective: The objective of this study is to assess changes in local economic outcomes before and after rural hospital closures. Data Sources: Rural hospital closures from January 1, 2005, to December 31, 2018, were obtained from the Sheps Center for Health Services Research. Economic outcomes from this same period were obtained from the Bureau of Labor Statistics, Bureau of Economic Analysis, Quarterly Workforce Indicators, U.S. Federal Reserve Economic Data, RAND Corporation state statistics database, U.S. Social Security Administration, and U.S. Census Bureau. Design: Difference‐in‐differences study of 2094 rural counties. Data Collection/Extraction: The primary exposure was county‐level rural hospital closures. The primary outcomes were county‐level unemployment rates; employment‐population ratios; labor force participation‐population ratios; per capita income; total jobs; health care sector jobs; disability program participation‐population ratios; percent of the population with subprime credit scores; total filings for bankruptcies per 1000 population; and population size. Principal Findings: A total of 104 rural counties experienced a hospital closure, compared to 1990 rural counties that did not. Rural hospital closures were associated with significant reductions in health care sector employment (−13.8%; 95% CI: −22%, −5.6%; p < 0.001), but not with changes in any other economic measure. For unemployment rates, employment‐population ratios, per capita income, disability program participation‐population ratios, and total jobs, we found evidence of adverse trends preceding hospital closures. Findings were robust to adjusting for county‐specific time trends, specifying exposure at the commuting zone‐level, and using alternate definitions of rurality to define sample counties. Conclusion: With the exception of a decline in jobs within the health care sector, there was no association between rural hospital closures and county‐level economic outcomes. Instead, economic conditions were already declining in counties experiencing closures compared to those that did not.